Intramolecular cation–π interactions in protonated phenylalanine derivatives. Issue 1 (8th December 2016) - Fu, Weiqiang; Carr, Patrick J. J.; Lecours, Michael J.; Burt, Michael; Marta, Rick A.; Steinmetz, Vincent; Fillion, Eric; McMahon, Terrance B.; Hopkins, W. Scott
Abstract : The structures and properties of a series of phenylalanine (Phe) derivatives have been investigated in a joint computational and experimental infrared multiple photon dissociation (IRMPD) study. Abstract : The structures and properties of a series of phenylalanine (Phe) derivatives have been investigated in a joint computational and experimental infrared multiple photon dissociation (IRMPD) study. IRMPD spectra in the 1000–2000 cm −1 region show that protonation is localized on the amine group in all cases. Intramolecular cation–π interactions between the ammonium group and the phenyl ring heavily influence molecular geometries and properties such as gas phase basicity and proton affinity. By varying substituents on the phenyl ring, one can sensitively tune the cation–π interaction and, therefore, the molecular structure and properties. Variations in molecular structures and properties as a function of phenyl ring substitution are shown to correlate with substituent Hammett parameters.